2006
DOI: 10.1111/j.1479-828x.2006.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of placental delivery to prevent post‐partum haemorrhage: Lessons learned from an abandoned randomised clinical trial

Abstract: It has been recognised that, if the length of the third stage of labour exceeds 30 min, then there is an increased risk of a post-partum haemorrhage. Recent information has suggested that 18 min is the optimal time for removal of the undelivered placenta to prevent a post-partum haemorrhage. A randomised trial comparing 20 vs. 30 min was stopped after an interim analysis because only eight of 1607 patients' placentas had not delivered by 20 min. A third stage of labour that exceeded 10 min was observed to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…More recent studies show that the incidence of PPH rises earlier during the third stage. Based on these findings, it has been suggested that interventions to prevent PPH should be undertaken earlier …”
Section: Introductionmentioning
confidence: 99%
“…More recent studies show that the incidence of PPH rises earlier during the third stage. Based on these findings, it has been suggested that interventions to prevent PPH should be undertaken earlier …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Shorter median durations of the third stage, down to 4 minutes, have been reported in the most recent studies. 16 These could be explained by an increased use of active management.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of blood loss associated with placental separation and delivery depends on how quickly the placenta separates from the uterine wall and how effectively the uterine muscle contracts around the placental bed and the uterine blood vessels (3). If the placenta is not delivered within 10 minutes, the risk of PPH increases (18). Therefore, any intervention for shortening the duration of the TSL and preventing complications becomes important.…”
Section: Discussionmentioning
confidence: 99%
“…Placental retention is defined as the failure of placental delivery within 30 to 45 minutes and it usually requires intervention to assist delivery (18). Failure of the retro-placental myometrium contraction is the usual cause of a retained placenta.…”
Section: Data Presented As Mean ± Standard Deviation or Median With Mmentioning
confidence: 99%